2015
DOI: 10.1002/lary.25243
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of superior semicircular canal thickness with advancing age

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 22 publications
1
21
2
Order By: Relevance
“…Despite the low rate of bone turnover of the otic capsule, it is known that age has a negative effect on the thickness of bone covering the superior semicircular canal (10,11). A retrospective review of high-resolution temporal bone CT scans demonstrated that the thickness of bone over the superior semicircular canal decreases by 0.005 mm per year with increasing age (10).…”
Section: Discussionmentioning
confidence: 98%
“…Despite the low rate of bone turnover of the otic capsule, it is known that age has a negative effect on the thickness of bone covering the superior semicircular canal (10,11). A retrospective review of high-resolution temporal bone CT scans demonstrated that the thickness of bone over the superior semicircular canal decreases by 0.005 mm per year with increasing age (10).…”
Section: Discussionmentioning
confidence: 98%
“…However, the age-dependent evolution of PSC thickness was different in males and females. As can be seen in Table 2 , men aged ≥ 45 years did not show a significant agedependent modification in PSC thickness, but from age 45 years onward PSC thickness decreased faster (0.0180 ± 0.0080 mm/year) than the prevision of Davey et al [2015] for SSC. In females, PSC thickness increased significantly until age 45 years (0.0200 ± 0.0080 mm/year) but it did not show a significant age-dependent modification from age 45 years onwards.…”
Section: Discussionmentioning
confidence: 62%
“…In view of our findings, age and sex influence the thickness of PSC and SSC differently. An age-dependent reduction in SSC thickness, in both males and females, has been previously reported [Davey et al, 2015]. However, PSC thickness did not significantly evolve with age in young males ( ≤ 45 years) but it decreased from age 45 years onwards.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…20 Further erosion may occur with age. 21 The average age at diagnosis is 46 years. 22 Dehiscence renders the membranous labyrinth unusually susceptible to sound and pressure changes.…”
mentioning
confidence: 99%